Peningkatan Kemampuan Mengenal Keaksaraan Awal Anak Usia 5-6 Tahun Melalui Media Kotak Pintar Di TK Islam Terpadu Asiah Kecamatan Mentawa Baru Ketapang Kabupaten Kotawaringin Timur - Arbayah; Panca Wahyu kusumaningrum; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
The main problem in this research is how to improve the early literacy skills of children aged 5-6 years through the smart box media. This type of research is Class Action Research which consists of two cycles where each cycle is carried out in 1 meeting. Research procedures include planning, implementation, observation, and reflection. The subjects in this study were 15 students in group B at the Integrated Asiah Islamic Kindergarten. The results showed that in the first cycle after being given the action in the first and second meetings, it was seen that the increase was not too significant, namely in cycle I the average yield was 51.7% with the Start Developing criteria (MB) and after taking action in cycle II there was an increase of the average yield percentage is 80.5% with Very Good Developing (BSB) criteria